Islam, democracy, and cosmopolitanism at home and in the world - Mirsepassi, Ali; Fernee, Tadd Graham (Cambridge University Press, 2016)
This book presents a critical study of citizenship, state and globalization in societies that have been historically influenced by Islamic traditions and institutions.